Pengaruh Financial Knowledge, Financial Attitude, Financial Self Efficacy, Income, Locus of Control, dan Lifestyle terhadap Financial Management Behavior Generasi Z di Kota Surabaya - Firda Khoirotun Nisa; Nadia Asandimitra Haryono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study investigates financial management behaviour among adolescents aged 9 to 24 years or referred to as Generation Z. It also analyzes the relationship between financial knowledge, financial attitude, financial self-efficacy, income, locus of control, and lifestyle. The object of this research is Generation Z in Surabaya and used the technique of purposive sampling and snowball sampling. The number of respondents obtained was 320 respondents by distributing questionnaires online. This research is conclusive causality and uses the AMOS software's structural equation modelling (SEM) analysis technique. The results show that financial knowledge, financial attitude, and financial self-efficacy do not affect financial management behaviour. It proves that although respondents' financial knowledge, financial attitude, and financial self-efficacy in a suitable category cannot guarantee their financial management behaviour will be good and vice versa. While income, locus of control, and lifestyle significantly impact financial management behaviour. Because the sample dominant are not financially independent, they can not manage financial independence to the greatest extent and do not have much experience related to finance. It was also caused by female respondents who often engage in impulsive buying. This study could be helpful to references for various parties, especially Generation Z, to be responsible for making financial decisions and wise in managing their finances.